AI IN EFL EDUCATION - PROMISE AND PERIL FOR RURAL INDONESIAN LEARNERS IN CENTRAL BORNEO - Marchia, Dian Sari (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The integration of Artificial Intelligence (AI) in English as a Foreign Language (EFL) teaching offers significant benefits as well as challenges, particularly for learners in remote areas of Central Kalimantan, Indonesia. This conceptual article examines the potential of AI-based technologies, such as individualized learning, automated feedback systems, and language practice applications, to enhance learner autonomy and facilitate language acquisition. On the other hand, this article also addresses important issues such as limited internet access, inadequate technological infrastructure, socio-cultural barriers, and the digital literacy gap between teachers and students. This study develops a fair and contextually appropriate framework for remote areas in Central Kalimantan by combining current empirical research and expert perspectives. The findings indicate that the success of AI in this educational setting is only achievable if it is adjusted to the specific environment, teachers receive adequate training, and the policies implemented are contextual. Additionally, ethical concerns arise regarding data privacy, overreliance on technology, and the potential negative impact on students' creativity and social skills. Experts emphasize that AI should not replace the role of human teachers, especially in remote rural areas that already experience inequality. The article concludes with recommendations for policymakers, educators, and technology experts to ensure the responsible and culturally sensitive use of AI, thereby promoting educational inclusion without exacerbating existing inequalities.